Oxidative DNA damage in reconstituting T cells is associated with relapse and inferior survival after allo-SCT - Karl, Franziska; Liang, C.; Böttcher-Loschinski, R.; Stoll, Andrej; Flamann, Cindy; Richter, Silja; Lischer, Christopher; Völkl, Simon; Jacobs, Benedikt; Böttcher, M.; Jitschin, R.; Bruns, Heiko; et al. (Blood, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-SCT) is the only curative treatment option for a number of hematologic malignancies. Its therapeutic potential relies on the potency of donor T cells to eliminate residual malignant cells, the so-called graft-versus-leukemia (GVL) effect. Disease relapse remains the most frequent treatment failure and is associated with poor outcome. Therefore, it is inevitable to decipher mechanisms that weaken GVL. In recent years, studies of tumor biology have revealed that metabolic remodeling of the micromilieu can critically regulate immune responses. Accumulation of reactive oxygen species leads to a metabolic condition known as oxidative stress, which can severely hamper T cells. Currently, only a few studies, mainly using preclinical models, have demonstrated the occurrence of oxidative stress after allo-SCTs. Therefore, we sought to investigate oxidative stress in a well-characterized group of patients who underwent allo-SCT and its impact on reconstituting T cells. We identified high concentrations of serum 8-hydroxydeoxyguanosine (8-OHdG) as an established biomarker for oxidative stress. 8-OHdG is one of the major products of DNA oxidation, which is normally rapidly removed. After allo-SCT, T cells accumulated oxidative DNA damage. High cellular 8-OHdG content (8-OHdGhi) was associated not only with signs of enhanced T-cell activation but also premature exhaustion. The inability of 8-OHdGhi T cells to efficiently target malignant cells or produce cytotoxic granzyme B and interferon gamma was associated with a significantly increased relapse risk and a shorter overall survival. Taken together, our novel findings could give reason to focus on bolstering DNA repair in reconstituting T cells as a means to improve GVL efficacy.
CRIS-Team Scopus Importer:2023-03-31